Ultrasound image guided injection of botulinum toxin for the management of spasticity: A Delphi study to develop recommendations for a scope of practice, competency, and governance framework - Stephen A. Ashford, PhD; Gary Morris, MSc; Michael J. Smith, PhD (Archives of Rehabilitation Research and Clinical Translation, 2023)
Objective: To establish a scope of practice, competency (through education) and governance framework for ultrasound image guided injection of botulinum toxin in the management of spasticity Design: Delphi study Setting: International, web-based survey Participants: A purposively selected multidisciplinary (physicians, physiotherapists, occupational therapists) panel of experts (n=15) in the use of ultrasound image guided injection of botulinum toxin for management of spasticity. Panel members were predominantly based in the UK (11/15). Interventions: In round 1, open-ended questions were posed relating to potential scope of practice for ‘ultrasound imaging in spasticity management’; (specifically relating to ultrasound image guided injection of Botulinum Toxin) education/competency and governance considerations. In round 2, respondents were asked to rate their level of agreement with the statements generated. Outcome measures: 5-point Likert scale used for rating the statements. Threshold for consensus agreement was set at 70% or above. Results: Three different scopes of practice relating to ultrasound imaging in spasticity management were accepted. The primary scope of practice was the use of ultrasound imaging to guide safe and accurate delivery of botulinum toxin. Relating to this primary scope, 7 competency requirements were agreed relating to areas including image optimization and interpretation, needle visualization and safety. A singular, broad governance statement was generated. Conclusion: Relating specifically to guided injection of botulinum toxin for management of spasticity, we present a scope of practice, competency, and governance framework. These are integrated within a framework approach to provide a mechanism for increased patient access to accurate, safe, and effective focal spasticity treatment. The framework supports focused training routes, greater inter-profession communication and wider clinical community engagement in spasticity management using this modality.